Dental problems and oral microbiome alterations in ulcerative colitis - Kucharski, Robert; Sobocki, Bartosz Kamil; Stachowska, Ewa; Bulman, Nikola; Kalinowski, Leszek; Kaźmierczak-Siedlecka, Karolina (Frontiers in Immunology, 2025)
Ulcerative colitis is a chronic disease that has not well-established etiology. The role of microbial dysregulation in its pathogenesis has been recently highlighted. Overall, microbiome alterations concern the reduction of bacterial abundance and diversity, resulting in gut microbiome imbalance negatively affecting immunological aspects. There is a link between ulcerative colitis and the oral microbiome. The changes of oral microbiome are found at many levels, from gently dysbiotic composition to the presence of the main periodontal microbes. The analysis of oral microbiome can be a part of personalized medicine due to the fact that it is a potential biomarker. Patients with ulcerative colitis may manifest dental symptoms/problems, such as periodontitis (strongly related to the red-complex pathogens—Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, and bacteria belonging to the other complexes, such as Fusobacterium nucleatum and Aggregatibacter actinomycetecomitans), dental caries, oral ulcerations, leukoplakia, halitosis, and others. Notably, the DMFT (Decayed, Missing, Filled Teeth) index is higher in these patients compared to healthy subjects. According to some data, oral lichen planus (which is a disease with an immunological background) can also be observed in ulcerative colitis patients. It seems that deep understanding of ulcerative colitis in association with oral microbiome, immunology, and dental manifestations may be crucial to provide complex treatment from a dental point of view.